Analysis of Polycyclic Aromatic Hydrocarbon in Airborne Particulate Matter Samples by Gas Chromatography in Combination with Tandem Mass Spectrometry (GC-MS/MS) - Nam Vu-Duc; Lan Anh Phung Thi; Thuy Le-Minh; Lan-Anh Nguyen; Huong Nguyen-Thi; Loan-Ha Pham-Thi; Van-Anh Doan-Thi; Huong Le-Quang; Hung Nguyen-Xuan; Thao Thi Nguyen; Phuong Thanh Nguyen; Dinh Binh Chu (Journal of Analytical Methods in Chemistry)
Polycyclic aromatic hydrocarbons (PAHs), the family of organic contaminations, have been shown to have negative effects on human health. However, until now, the comprehension on occurrence, distribution, and risk assessment of human exposure to PAHs has been limited in Vietnam. In this work, a capillary gas chromatography coupled with electron impact ionization tandem mass spectrometry (GC-EI-MS/MS) has been introduced for analysis of 16 PAHs in some particulate matter samples. PAHs have been separated on the TG 5 ms capillary gas chromatographic column and detected by tandem mass spectrometry in multiple reaction monitoring mode. The PAHs in the particulate matter (PM 2.5 and PM 10) samples were extracted by ultrasonic-assisted liquid extraction and cleaned up by an acidic silica gel solid phase extraction. The linearity range of all analyzed PAHs was from 5 to 2000 ng mL−1 with R2 ≥0.9990. Limit of detection (LOD) of PAHs in particulate matter sample was from 0.001 ng m−3 (Br-Naph) to 0.276 ng m−3 (Fln). The recovery of PAHs was investigated by international proficiency testing samples. The recoveries of PAHs in proficiency testing sample ranged from 79.3% (Chr) to 109.8% (IcdP). The in-house validated GC-EI-MS/MS method was then applied to analysis of some particulate matter samples that were collected in the Hanoi areas. The total concentrations of PAHs in several brands of samples collected from Hanoi were found in the range of 226.3 ng m−3–706.43 ng m−3. Among the studied compounds, naphthalene was found at high frequency and ranged from 106.5 ng m−3 to 631.1 ng m−3. The main distribution of the PAHs in particulate matter samples was two-ring and three-ring compounds.